Physico-chemical characterization of botanero cheese - Espinoza-Ortega, Angélica; Montes de Oca Flores, Eric (Indian Journal of Dairy Science, 2020)
The objective of the present study was to characterize the physico-chemical properties of artisanal botanero cheese and the raw material (milk) used to make this cheese. Ten cheese dairy were sampled; four samples of cheese and milk were taken from each dairy for physico-chemical analysis. A flow diagram of the steps in the cheesemaking process was formulated, documenting the exact quantities of added ingredients and time required for each and every step. In milk, fat content, protein content, density, acidity, and pH were measured, and in cheese, ash, moisture, and salt content were measured. The resulting data were submitted to a principal component analysis and compared with the parameters outlined in standard COFOCALEC-700-2004 for raw cow’s milk and the standard NMX-462-1984 for manchego-type cheese. High variability in the sampled parameters was found both among and within dairies. The milk samples complied with the minimum permissible limits for most of all analyzed parameters.